Follicular development and ovulation in extremely obese women receiving depo-medroxyprogesterone acetate subcutaneously - Segall-Gutierrez, Penina; Taylor, DeShawn; Liu, Xinwen; Stanzcyk, Frank; Azen, Stanley; Mishell, Daniel R. (Contraception (Stoneham), 2010)
Subcutaneous depo-medroxyprogesterone acetate (DMPA-SC) has not been studied in the extremely obese population (BMI ≥40 kg/m2). The purpose of this 26-week prospective experimental study was to determine incidence of ovulation and follicular development among women with Class 1, 2 and 3 obesity after receiving DMPA-SC. Five normal-weight, five Class 1-2 obese, and five Class 3 obese women received subcutaneous injections of 104 mg DMPA-SC at baseline and 12 weeks later. Weekly progesterone levels, bimonthly estradiol (E2), and monthly medroxyprogesterone acetate (MPA) levels were measured by immunoassay methods for a total of 26 weeks in each subject. Ovulation did not occur in any subject more than 1 week after the first injection. There was large intersubject and intrasubject variability in E2 levels, and fluctuating E2 levels were more frequent among obese women than normal-weight women. Median MPA levels remained above the level needed to prevent ovulation but, compared with normal-weight subjects, were lower among Class 1-2 obese and lowest among Class 3 obese subjects. Fluctuating E2 levels reflective of follicular development occurred more often among Class 1, 2 and 3 obese women than normal-weight women after DMPA-SC injections. Median MPA levels were consistently lowest among Class 3 obese women but remained above the level needed to inhibit ovulation. Further studies should more fully address the pharmacokinetics of DMPA-SC in extremely obese women.